Enhancing Accessibility for Saudi Deaf and Hard-of-Hearing Audiences: Sound Representation in SDH Subtitling of Saudi Series - Haider, Ahmad S.; Sahari, Yousef; Saed, Hadeel; Tair, Sausan Abu (Journal of Disability Research, 2025)
Subtitling for deaf and hard-of-hearing audiences is an accessibility mode of audiovisual translation that aims to enhance the experience of its target audiences by rendering auditory codes in a written form. Naturally, this entails representing sound effects in the caption through intersemiotic translation. Verbalizing these sounds may include various elements which can either represent the sounds directly or indirectly. This paper aims to examine the degree to which sounds are represented in the Arabic captions of Saudi works. The analysis revealed that a substantial proportion of captions merely described the action that produced the sound rather than conveying sonic qualities. Other captions were more informative by containing sound descriptors, information on frequency, distance, sound source, or a combination of these elements. The study recommends that further guidelines be developed to improve the representation of sound effects in captions, especially in the Arabic language.